(3CKQ SdWGJ GdfjGHI Ydi GdeQcR GdbGfhfj ddeJge (B/s - (3efTGhj, eMeO CMeOs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2019)
(3jJMOK GdcJGH Yf CKQ SdWGJ GdfjGHI Ydi GdeQcR GdbGfhfj ddeJge GdOcJhQ eMeO CMeO GdefTGhj MjK Ef GdVQhQI GdYdejI hGdbGfhfjI GdJj JaQV acQI GdeSGhGI hGdehGRfI Hjf GdfjGHI GdYGeI hGdeJge CYWJ gPg GdeSCdI ecGfI gGeI aj SGMI GdELQGAGJ GdLfGFjI dGQJHGWgG GdhKjb HMb GdOaGY hCUd GdHQGAI hGdMb aj eMGceI YGOdI GdCeQ GdPj jLYd ef Mb GdeJge aj eMGceI YGOdI dG jJMOO abW ef NdGd GdGQJHGW GdJdbGFj hGdefWbj HMb GdOaGY hEfeG jJMOO MbjbI HeSGhGI gPG GdMb eY eG efM ddjfGHI GdYGeI ef SdWGJ jSJhLH eYg VQhQI GdfXQ aj SdWGJ GdfjGHI GdYGeI GSJLGHI ddCgejI GdELQGFjI hGdGYJHGQGJ GdYedjI GdJj JaQVgG GdeHGOF GdEfSGfjI hGdbGfhfjI hGdCNdGbjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B179-195.s
Keywords: (3GdOaGY Yf GdeJge (B((3ELQGAGJ LfGFjI(B)s; (3GdfjGHI GdYGeIs -- (3bhGfjf hJTQjYGJs; (3bGfhf GdELQGAGJ GdLfGFjIs; (3GdJMbjb GdGHJOGFj s; (3SdWI GdfjGHI GdYGeIs; (3bVGA GdEMGdIs